Bassam Tibi’s Euro-Islam - Ilic D., Zoja B (Sociološki pregled, 2017)
The aim of this paper is to show the intellectual and scientific work of the German sociologist of Syrian descent, Bassam Tibi, mainlyby the presenting his concept to the Euro-Islam, which is useful on international social and political level. The EuroIslamic framework includes advice and guidelines to help Muslims and non-Muslims to constructively overcome the misunderstandings they encounter in the countries of Western Europe elsewhere. Also, Tibi suggests ways Muslims in the Muslim countries can painlessly go through the transition, which will lead them forward.Considering the fact that the countries of the former Yugoslavia are the homeland of a number of Muslims, Tibi’s work can be useful for sociological analysis and guidelines for state policies, among others, in Serbia.